Urban Structure Transformation between the Role of Urban Planning Methods and Real Estate Market Force – Case Study: the New Millennial Cities in Egypt - Said Hassanien Al-Sayed; youssef elsayed (JES: Journal of Engineering Sciences, 2021)
ABSRACT:Over the past forty years, many new cities have emerged in Egypt, including millennial cities. It is noticed that there are many urban changes in these cities since the beginning of their inception until now. Including city area, patterns, characteristics, rates and percentages of land uses within the city as the decrease or increase of some elements ratios, disappearing of some uses, in addition to transfer of some uses from its usual place to another inside the city. UN- Habitat conclude that many reasons have led to these changes as the change of housing policies and the strong participation of private sector who use an innovative model based on customer preferences in development of many cities areas and also the change of housing policies. This new model depends on replacing the domestic basic services in the centers by green areas and recreational.The research aims to monitor the changes and urban transformations occurring within the major millennial cities within Greater Cairo region in Egypt since the beginning of its inception at late 1970s up to now, studying the different reasons that led to these changes, then deriving some indicators and set guide lines and put foundations and standards that help to develop urban planning of major new Millennial cities structure in Egypt.